Temptation and Intimidation in the Holy Quran and the Sunna And their Teaching – learning Perspectives (Journal of the College of Education for Women, 2019)
Methods of teaching plays an important vole in the educational processbecause is the link between the teacher and the learner. The process ofteaching doesut fulfill the desirable results unless the methods of guiding andteaching are provided and through a qualified educationalist capable ofcommunicating the syllabus to the students in an easy and clear way. In spiteof the diversity of the methods of teaching ,there is no one way suitable for allthe educational purposes , all the sciences ,all the subjects ,all the levels ofgrowth ,levels of teaching, maturity and intelligences ,all teachers andeducationalists and all the circum stances surrounding the teaching processes.The teacher is the one who chooses the method that suits the educationalpurpose to achieve, the subjects he teacher ,the kind of lesson ,the level ofgrowth and learning ,level of maturity ,intelligence and achievementof his students, the available requirements .when we talk about the methodsof teaching Islamic Education we have to talk about the first educationalistour prophet Muhammad who did handle the process of education andteaching as he was ordered by Almighty God who says (( My God ordered meto teach you what you are ignorant of from what he has taught me)).The researcher in this study sheds light on one style of education whichhas already been mentioned many times in the Holy Quran and the Sunnite ofour prophet which is through the method of temptation and intimidation.The aim of the present study is to indemnify out he two stylestemptation and intimidation in the Holy Quran and the Sunni and theirpedagogical – learning perspectives. To achieve this aim, the researcher usedthe analytical descriptive method to account for the number of uses in theHoly Quran and the sunna by calculating the repeated words that carry inmeaning and pronunciation the meaning of temptation and intimidation.The researcher has reached into the following conclusions: 1-The most repetitive verses in the Holy Quran for the temptation in which"paradise "is used are about (113).2- The most repetitive verses for the intimidation in which "fear " in used areabout (121).3- As for the Sunna, the temptation saying for the "prayer" comes on the topof the list, about (374).4- While the intimidation in literature include about (230).The researcher suggested dictating the two styles in the collegeteaching. Also the researcher suggested the following recommendations :1- Holding training courses for the teacher of Islamic education to know suchstyles and how to teach them .2- Making use of the prophets teaching styles in educating his followers andputting them on the right track including the implantation of the right principlesfor the students.3- Shedding light on the influence of the tow styles in teaching the collegestudents.4- Identifying the influence of other styles of the prophet on other stages.